APLIKASI WEBSITE UNIT KEGIATAN MAHASISWA GITA PASUATIKA MENGGUNAKAN MACROMEDIA FLASH 8 - Kun Wiryantomo; Ristyawati., SKom, MMSI Ristyawati., SKom, MMSI (Jurnal Sistem Informasi, 2007)
Along with the development of the age and increasingly sophisticated technology, almostall people in the world using the Internet where the Internet provides information ofvarious aspects of the field by means of a container known as a Web site.Student Activity Unit website Pasuatika Gita, is a website that contains information aboutthe profile and activities of the student choir STMIK STI & K. JakartaStudent Activity Unit website making this Pasuatika Gita Macromadia applicationprogram Flash 8, Adobe Photoshop 7.0, and as the browser is Internet Explorer.